2006
DOI: 10.1080/00207450600808768
|View full text |Cite
|
Sign up to set email alerts
|

Mild Executive Dysfunctions in Undergraduates Are Related to Recollecting Words Never Presented

Abstract: The aim of this study was to explore whether individual differences in executive function in undergraduate students (n = 72) contribute to false recall and recognition as obtained with the Deese/Roediger-McDermott (DRM) paradigm. Participants were subjected to the DRM paradigm and also were given a test designed to assess executive function--the Random Number Generation task (RNG). A relationship was found between heightened seriation on the RNG (indicating a deficiency in the ability to inhibit cognitive sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(45 reference statements)
1
11
0
1
Order By: Relevance
“…Researchers have also studied a number of cognitive variables as predictors of false memories in the DRM. A growing body of research has demonstrated a negative correlation with working memory (Parker, Garry, Engle, Harper, & Clifasefi, 2008;Peters, Jelicic, Haas, & Merckelbach, 2006;Peters, Jelicic, Verbeek, & Merckelbach, 2007). This relationship appears to be stronger under conditions that call for a high degree of source monitoring, such as when participants are forewarned about the types of memories errors the DRM tends to produce (Watson, Bunting, Poole, & Conway, 2005).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Researchers have also studied a number of cognitive variables as predictors of false memories in the DRM. A growing body of research has demonstrated a negative correlation with working memory (Parker, Garry, Engle, Harper, & Clifasefi, 2008;Peters, Jelicic, Haas, & Merckelbach, 2006;Peters, Jelicic, Verbeek, & Merckelbach, 2007). This relationship appears to be stronger under conditions that call for a high degree of source monitoring, such as when participants are forewarned about the types of memories errors the DRM tends to produce (Watson, Bunting, Poole, & Conway, 2005).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Working memory involves the active maintenance and manipulation of information and recruits dorsolateral prefrontal regions (Curtis & D'Esposito, 2003), the same regions that are involved in retrieval monitoring in the DRM task and other tasks. Lövdén (2003) found that individual differences in working memory correlated negatively with the DRM illusion and other false-memory tasks (see also Parker, Garry, Engle, Harper, & Clifasefi, 2008;Peters, Jelicic, Haas, & Merckelbach, 2006;Peters, Jelicic, Verbeek, & Merckelbach, 2007;Peters, Smeets, Giesbrecht, Jelicic, & Merckelbach, 2007). Moreover, the relationship between working memory and the DRM illusion can be stronger under conditions that require a high degree of monitoring (McCabe & Smith, 2002;Watson, Bunting, Poole, & Conway, 2005), and Unsworth and Brewer (2010) used latent variable analysis to show that source monitoring mediates the relationship between working memory and DRM false memory.…”
Section: Closure: What We Do Not Know About the Problemmentioning
confidence: 99%
“…We developed an adapted version of the DRM paradigm (Deese, 1959;Roediger & McDermott, 1995) so as to tap memory efficiency, memory errors, and source attributions. Participants were administered a Dutch version of the DRM paradigm consisting of eight selected word lists drawn from a normative study Peters, Jelicic, & Merckelbach, 2007;Peters, Jelicic, Haas, & Merckelbach, 2006a). Each list consisted of 15 words (e.g., bed , nap, pillow, snooze) semantically related to a nonpresented critical lure word (e.g., sleep ).…”
Section: Methodsmentioning
confidence: 99%